Trump University asset protection 101 : - Childers, J. J. (John Wiley & Sons, 2008)
Three obstacles to wealth-lawsuits, income taxes, and estate taxes-can and will destroy the financial achievements of those who fail to properly safeguard their assets. In this book, attorney and tax strategist J.J. Childers lays out a plan for combating these forces so that anyone willing to learn and apply the secrets of the wealthy can do so in a smart, simple, and effective way.